Impelementasi Hardware Redundancy Pada Switching Pintu Otomatis Dengan Metode Cold Standby Dan Watchdog - Muhammad Rifqi Muzaki; Sabriansyah Rizqika Akbar; Widhi Yahya (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Electronic devices must have a lifetime limit and may be damaged at any time. A system consisting of several electronic devices will fail if the crucial component is damaged. Therefore, crucial components in a system should be more reliable. To improve system reliability a mechanism such as Hardware Redundancy can be applied. Hardware Redundancy is a mechanism to improve reliability by duplicating important components as backup. There are several types of Hardware Redundancy mechanisms, one of which is Cold Standby Redundancy which uses the unpowered backup concept. The Cold Standby concept is to add a duplicate of an important component that standby without a power supply and will be active when the component is damaged. In this study Cold Standby Redundancy is applied to an automatic door lock system based on Arduino Uno and RFID. An important component of the system is Arduino Uno which acts as a controller in the system. Implementation of cold standby redundancy on this system uses a third party device (Arduino Nano) as the fault detector of main Arduino Uno (master). Through I2C serial communication the master sends keep-alive status periodically to the fault detector as a sign of whether it is still operating or is being damaged. In addition there is a switch device in charge of switching the system control to master or slave. The fault detector sends the trigger to make a switch to the switch device when it detects damage to the master. Based on the results of tests that have been done, system reliability increases after applying the Cold Standby Redundancy mechanism. System reliability value increased by 15.45% for a year operating time.